Downy Mildew of Basil in South Florida - Shouan Zhang; Pamela D. Roberts; Richard Raid (EDIS)
PP271, a 3-page illustrated fact sheet by Shouan Zhang, Pamela D. Roberts, and Richard Raid, describes this new destructive disease that results in yellowing and cupping of the leaves of basil and ornamental plants related to it — distribution, symptoms, and control. Published by the UF Department of Plant Pathology, September 2009.